1993
DOI: 10.1128/jvi.67.8.4464-4473.1993
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the phosphorylation sequence in the cytoplasmic tail of the varicella-zoster virus Fc receptor glycoprotein gpI

Abstract: Varicella-zoster virus (VZV) glycoprotein gpI, the homolog of herpes simplex virus gE, functions as a receptor for the Fc portion of immunoglobulin G. Like other cell surface receptors, this viral receptor is highly phosphorylated in cell culture. To identify the precise location of the cellular kinase-mediated phosphorylation, we generated a tailless deletion mutant and several point mutants which had altered serine and threonine residues within the cytoplasmic domain of gpI. The mutated and wild-type genes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 31 publications
3
44
0
Order By: Relevance
“…We have shown, by all criteria employed so far, that the BHV-1 proteins produced by PRV were indistinguishable from those made by BHV-1 virus itself: we used Western blot analysis, pulse-chase radiolabeling experiments, endoglycosidase digestion, immunofluorescence, and in vitro translation to arrive at this conclusion (data reviewed but not shown in this paper). We did not analyze phosphorylation or sulfation, modifications that have been reported or predicted for other gE-gI homologs (7,8,25,39,40). We did insert the BHV-1 gI gene into the PRV gI locus, but we found that expression was considerably less efficient (15-fold lower than that from gG).…”
Section: Discussionmentioning
confidence: 98%
“…We have shown, by all criteria employed so far, that the BHV-1 proteins produced by PRV were indistinguishable from those made by BHV-1 virus itself: we used Western blot analysis, pulse-chase radiolabeling experiments, endoglycosidase digestion, immunofluorescence, and in vitro translation to arrive at this conclusion (data reviewed but not shown in this paper). We did not analyze phosphorylation or sulfation, modifications that have been reported or predicted for other gE-gI homologs (7,8,25,39,40). We did insert the BHV-1 gI gene into the PRV gI locus, but we found that expression was considerably less efficient (15-fold lower than that from gG).…”
Section: Discussionmentioning
confidence: 98%
“…The second important determinant regulating gpl trafficking is the highly acidic stretch of amino acids (587-DDFEDSESTDTEEE602) that contains four hydroxylated residues (Ser593, SerS95, ThrS96, ThrS98), two of which (ThrS96 and 598) fall into consensus sites for casein kinase II phosphorylation. Previous work showed that threonines 596 and 598 can be phosphorylated in vivo and in vitro by purified casein kinase II (Yao et al, 1993b). Accordingly, the removal of two threonines leads to a considerable redistribution of gpl to the cell surface, whereas the single mutation of any one of the two threonines does not affect the steady-state distribution of the protein.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to furin, other secretory pathway membrane proteins have been argued to be substrates for CKII, including the cytoplasmic tails of the signal sequence receptor (SSR) (Ou et al, 1992), calnexin (Ou et al, 1992), synaptotagmin (p65) (Bennett et al, 1993;Davletov et al, 1993), the varicella-zoster virus Fc receptor (Yao et al, 1993), the polymeric immunoglobulin receptor (Casanova et al, 1990), and both the cation-independent and -dependent mannose 6-phosphate receptors (Meresse et al, 1990;Rosorius et al, 1993;Korner et al, 1994). The phosphorylation of the rough endoplasmic reticulum (RER)-resident proteins SSR and calnexin together with profurin ( Figure 4) argues for a RER-localized CKII activity that phosphorylates a number of membrane proteins.…”
Section: Discussionmentioning
confidence: 99%